A method for improving measurement accuracy of cylinders in dimensional CT metrology. (December 2015) - Xue, Lin; Suzuki, Hiromasa; Ohtake, Yutaka; Fujimoto, Hiroyuki; Abe, Makoto; Sato, Osamu; Takatsuji, Toshiyuki
Abstract: Measurement quality of industrial cone beam X-ray computed tomography (CT) is influenced by many types of artefacts, therefore, industrial-level accuracy is difficult to attain. In order to avoid the influences of these artefacts, this paper proposes a new method for measuring cylindrical surface that is a common geometric structure in mechanical parts. The proposed method fits cylindrical surface from a sinogram image directly. Compared with a standard way for dimensional CT metrology, higher measurement accuracy and less measurement time can be achieved. Mainly, the method consists of edge points detection of a sinogram image and cylindrical surface fitting. The performance of the method is evaluated by use of both simulation data and actual data. Highlights: The method can fit cylindrical surface from a projection image directly. The method can measure cylindrical surface with a higher accuracy. The method can complete measurement by use of much less measurement time.